Gelatinous silver colloid nanoparticles: synthesis, characterization, and their antibacterial activity - Darroudi, M.; Ahmad, M. B.; Mashreghi, M. (INOE Publishing House, 2014)
The major method used for synthesis of silver nanoparticles (Ag-NPs) is the chemical wet reduction method. The problem with the chemical reduction method is that the synthetic process is expensive and can also have toxic substances absorbed onto them. To overcome this, the “green” method provides a feasible alternative. This study demonstrated a green and facile approach for one-step synthesis of Ag-NPs at ambient temperature. It was found that gelatin can play double roles in the proposed synthesis, including a stabilizer and a reducing agent. Silver ions can be rapidly reduced by gelatin at room temperature due to its dominant reducing capacity. The effects of temperature and reaction times on particle size of Ag-NPs were studied. The capability in size control can be evidenced by TEM images. The antibacterial properties of the Ag-NPs were tested against different gram-positive and gram-negative bacteria. This approach reveals that green mediated method is a promising facile route for the size-controlled synthesis of gelatinous colloid Ag-NPs in aqueous solution with good antibacterial properties for different applications (e.g., in medical applications).